Application of Planar Laser-Induced Fluorescence for Interfacial Transfer Phenomena; Energies; Vol. 16, iss. 4 - Dulin V. M. Vladimir Mikhaylovich; Cherdantsev A. V. Andrey Vladimirovich; Volkov R. S. Roman Sergeevich; Markovich D. M. Dmitry Markovich (2023, 2023)
Title screen